Vindija Cave and the modern human peopling of Europe - Janković, Ivor (Array, 2006)
Vindija cave in Croatia has yielded the youngest securely dated Neandertal skeletal remains in Central/Eastern Europe. In addition, these remains have been found in association with archaeological material exhibiting Upper Paleolithic elements. Due to its geographic location and date, the Vindija remains are particularly crucial for the understanding of initial modern human peopling of Europe and the nature of the Neandertal demise. The significance of archaeological finds and hominin fossils from this site is discussed in the light of new finds at Vindija and recent developments in the fields of paleoanthropology and prehistoric archaeology. Further, the impact of revised chronology for several crucial specimens and sites throughout Europe, and including Vindija, is discussed. We argue that the association of an early Upper Paleolithic industry and late Neandertals at Vindija is not likely to be a result of artificial mixing of specimens from different strata, but rather that these artifacts are reasonably considered to be products of the Vindija Neandertals. Although similar archaeological samples in Europe have traditionally been regarded as Aurignacian and automatically assigned to anatomically modern humans, we believe many of earliest Upper Paleolithic assemblages are in fact derived from local Mousterian, and the question of which population is responsible for the production of these assemblages remains unclear. The only clear association of hominin remains and the Initial Upper Paleolithic thus far has been Neandertals with the Châtelperronian. Further, Aurignacian can no longer be considered a single Pan-European industrial complex, but rather represents a number of local early Upper Paleolithic industries. In this light the association of Neandertals and Early Upper Paleolithic is not surprising. Unfortunately the relatively short time frame of the populational overlap between late Neandertals and early moderns, possible differential site use, and taphonomic factors, (erosion etc.) will make such in situ evidence unlikely to be preserved. Therefore, the Vindija G1 layer is a rare and important find. Anthropological analyses demonstrate that the late Neandertals at Vindija exhibit a more modern pattern of morphology compared to most other European Neandertals. We believe that both the anatomical and archaeological characteristics of Vindija are best explained by the Assimilation model of modern human origins.